Synthesis, characterization of thiolated karaya gum and evaluation of effect of pH on its mucoadhesive and sustained release properties - Bahulkar, Swati S.; Munot, Neha M.; Surwase, Sachin S. (Carbohydrate Polymers, 2015)
Present study aims at synthesis and characterization of thiolated gum karaya by reacting karaya gum with 80% thioglycolic acid resulting in esterification and immobilization of thiol groups on polymeric backbone. Immobilized thiol groups were found to be 5.026 mM/g determined by Ellman's method. It was characterized by FTIR, DSC and XRD. Directly compressible tablets prepared using thiolated gum displayed more disintegration time, swelling and mucoadhesion with increase in pH of medium simulating gastric and intestinal environment than plain gum. Controlled drug release for more than 24h by Fickian diffusion following Korsemeyer-Peppas model was observed with Metoprolol Succinate as a model drug as compared to plain gum which released more than 90% of the drug within 2 h. Synthesized thiomer showed no cytotoxicity determined using HepG2 cell line. According to these results, thiolated gum karaya seems to be promising excipient for the development of mucoadhesive drug delivery systems. (C) 2015 Elsevier Ltd. All rights reserved.

Mechanically tunable curcumin incorporated polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Azad, Lal Busher; Surwase, Sachin S.; Torris, Arun A. T.; Badiger, Manohar V. (Chemistry of Materials, 2016)
We report here on the one-pot synthesis and characterization of curcumin incorporated polyethylene glycol polyurethane (PU-CUR) hydrogels using PEG-4000, 4, 4'-methylenebis (cyclohexyl isocyanate), curcumin in the presence of a cross-linker, 1,2,6 hexanetriol (HT). Besides the physical entrapment, curcumin also provides a partial cross linking in the 3-D structure of the hydrogel. The degree of swelling in hydrogels could be controlled by varying the amount of HT as well as curcumin. The structural characterization of hydrogels was performed using Fourier transform infrared spectroscopy, high-resolution mass spectrometry, UV and fluorescence spectroscopy. The wide-angle X-ray scattering studies revealed the existence of crystalline domains of PEG, and the small-angle X-ray scattering studies showed the presence of lamellar microstructures. Porous structure in the hydrogel was created by cryogenic treatment and lyophilization. Scanning electron microscopy and microcomputed tomography imaging of hydrogels showed the presence of interconnected pores. The mechanical strength of the hydrogels was measured using a universal testing machine. The observed tensile and breaking compression strengths for the equilibrium swollen gels were found to be in the range of 0.22-0.73 MPa and 1.65-4.6 MPa, respectively. Detailed in vitro biological experiments showed the biocompatibility of gels, cytostatic dosage of curcumin, selective toxicity toward cancer cell lines, and antibacterial property. These gels show promising applications as scaffolds and implants in tissue engineering.

Tailoring the properties of mPEG-PLLA nanoparticles for better encapsulation and tuned release of the hydrophilic anticancer drug - Surwase, Sachin S.; Munot, Neha Manish; Idage, Bhaskar B.; Idage, Susheela B. (Drug Delivery and Translational Research, 2017)
Gemcitabine is used as a first-line drug for treating many solid tumours. However, it suffers from a major drawback of strong side effects and short plasma half-life because of degradation by enzyme when administered intravenously. Polyesters and copolyesters are the most widely used and preferred class of biodegradable polymer. In the present work, efforts have been made to prepare poly(ethylene glycol) monomethoxy ether-poly(l-lactide) (mPEG-PLLA), a biodegradable amphiphilic copolymer with a view to improve the entrapment and tuned release of hydrophilic drug gemcitabine. The different mPEG-PLLA copolymers were synthesized with the varying ratios of mPEG and characterized by different techniques namely FTIR and ¹H NMR spectroscopy, solution viscosity, differential scanning calorimetry (DSC) and gel permeation chromatography (GPC). Gemcitabine-loaded nanoparticles were prepared using mPEG-PLLA copolymers by two methods i.e. nanoprecipitation and double emulsion solvent evaporation. The nanoprecipitation method showed very less entrapment and polymer solubility in the acetone-water mixture leading to uncontrolled polymer precipitation. The difficulties encountered in the nanoprecipitation method were overcome with the help of the double emulsion (w/o/w) solvent evaporation technique. It has been observed from the results that biodegradable copolymer nanoparticles protect the drug from degradation and also help in controlling the release of encapsulated drug. The properties of nanoparticles can be tailored by varying the composition of mPEG in order to get improved entrapment efficiency and desired drug release. The nanoparticles were assessed for their in vitro cytotoxicity (MTT and FACS) and cellular uptake (fluorescence microscopy) study which showed very promising results. Nanoparticles were also studied for their in vivo release after intravenous administration to Wistar albino rats, which successfully showed controlled drug release for more than 14 days.